2018
DOI: 10.4103/jrms.jrms_135_18
|View full text |Cite
|
Sign up to set email alerts
|

Effect of diabetes mellitus type 2 on salivary glucose, immunoglobulin A, total protein, and amylase levels in adults: A systematic review and meta-analysis of case–control studies

Abstract: Background:Saliva is a fluid with the complex compound which can be used as diagnostic markers for type 2 diabetes (T2D). This meta-analysis evaluated salivary glucose, immunoglobulin A (IgA), total protein, and amylase levels in adult T2D compared with the controls as well as the correlation of salivary glucose levels with serum glucose and hemoglobin A1C (HbA1c) levels in both groups.Materials and Methods:Web of Science, Scopus, PubMed, and Cochrane Library databases were searched up to July 2017. A random-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 32 publications
1
5
0
1
Order By: Relevance
“…The differences in salivary amylase levels depending on the method of saliva collection under fasting conditions are uncertain, since differences with higher levels were observed under both fasting [ 34 , 36 , 48 , 60 ] and non-fasting conditions [ 11 , 30 , 32 , 41 , 61 ]. The heterogeneity of the results depending on the type of diabetes, the type of insulin treatment or control of the disease may also depend on whether the sample is collected under fasting or non-fasting conditions [ 62 ]. Conducting studies with uniform criteria would enable results to be unified for comparison.…”
Section: Discussionmentioning
confidence: 99%
“…The differences in salivary amylase levels depending on the method of saliva collection under fasting conditions are uncertain, since differences with higher levels were observed under both fasting [ 34 , 36 , 48 , 60 ] and non-fasting conditions [ 11 , 30 , 32 , 41 , 61 ]. The heterogeneity of the results depending on the type of diabetes, the type of insulin treatment or control of the disease may also depend on whether the sample is collected under fasting or non-fasting conditions [ 62 ]. Conducting studies with uniform criteria would enable results to be unified for comparison.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, salivary proteomic research has focused on the screening of novel biomarkers for oral and related diseases, including lactoferrin, interleukin-6, and matrix metalloproteinase-8 (Castagnola et al, 2017;Bermejo-Pareja et al, 2020;Kc et al, 2020;Boroumand et al, 2021). In addition, diabetes affects the composition of saliva, and alterations may impact the incidence or signs of oral lesions (Abd-Elraheem et al, 2017;Naseri et al, 2018). Overall, the impact of diabetes on salivary proteins has attracted the attention of many researchers.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we examined 30 pregnant women and 30 non-pregnant women, the results of which were consistent with the above-mentioned studies. The reason for this consistency of the results, despite the differences between the study groups, can be attributed to the methods of collecting samples and measuring serum and salivary markers (13,18). Furthermore, Soares et al measured and compared the blood and salivary levels of glucose and finally found no correlation between the blood and salivary glucose concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…The serum glucose and urea levels were also determined using glucose and urea diagnostic kits (5). between serum and salivary glucose levels and a correlation between serum and salivary urea levels, respectively (13,18). Naseri et al, in a review of more than 373 studies, concluded that there was a correlation between serum and salivary glucose levels (13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation